Jakość życia społeczności lokalnej - propozycja formułowania uspołecznionej oceny - Głuszczuk, Dariusz (Life Quality of the Local Society - a Proposal of Formulating a Socialized Evaluation, 2007)
Researching life quality involves solving several problems. They can be depicted in three questions: - What is the scope of meaning of life quality? - How can life quality be measured? - What determines the objectivization of formulated evaluations? This article attempts to answer these questions, which results in a definition-like description of life quality, general systematic of measurement methods of this category, a discussion about the objectiveness of formulated evaluations, and a proposal of conducting a survey. The author believes that survey techniques facilitate socialization of the process of life quality assessment (the evaluee becomes the evaluator).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 379-390